Detecting Financial Statement Fraud Using the Hexagon Fraud Theory Approach in Financial Sector Companies - Khoyumi Khoyumi; Adistya Puspa Inggani; Siti Nur Hadiyati (Publikasi Indonesia, 2024)
Good companies do not commit fraud and provide accurate and relevant information. Therefore, financial reports must be made as well as possible in order to provide accu-rate information to its users. This research is quantitative in nature to analyze the influence of the Fraud Hexagon Theory which is proxied by sixteen variables, consist-ing of four variables from the stimulus element (financial targets, external pressure, financial stability, personal financial needs), three variables from the opportunity ele-ment (supervision ineffectiveness, auditor quality and nature of the industry), two variables from the rationalization element (auditor turnover and value accruals), two variables from the capability element (director turnover and CEO education), two variables from the ego element (CEO duality and the number of CEO photos in the annual report), and three variables from collusion elements (political connections, audit fees and collaboration with government projects) on fraudulent financial statements. This research uses secondary data with purposive sampling. In 2019-2022, there are 63 financial sector companies listed on the Indonesian Stock Exchange. The results of this research prove that financial targets, financial stability, supervisory ineffective-ness, nature of industry and CEO duality influence financial report fraud.